Structural and Electrical Properties of Samarium-doped Ceria Electrolyte - Hai, Dang Thanh; Hung, Vu Van; Thu, Pham Ngoc; Dung, Lo Ngoc; Huong, Le Thi Thanh; Anh, Hoang Thi Minh; Thu Lam, Le (VNU Journal of Science: Mathematics - Physics; Vol 38 No 1DO - 10.25073/2588-1124/vnumap.4660, 2022)
Effect of dopant on structural and electrical properties of samarium-doped ceria (SDC) electrolyte was investigated using statistical moment method. Our results showed the lattice expansion due to doping and local distortion resulting from preferential distribution of oxygen vacancies around dopants. The ionic conductivity of SDC crystals is in more than three orders of magnitude larger than that of pure ceria. However, the presence of dopant in cation edge and the first nearest neighbor positions around migrating vacancy gives rise to the blocking and trapping effects on the vacancy transport. The maximum value of the ionic conductivity was found for the samples with  the dopant concentration x = 0.15. These results can be compared to the one of the published data of boththe  theoretical and experimental investigations.